POSITIONING AND DIFFERENTIATION OF EDUCATION SERVICES - Hepriyanti, Lisa; Rahma, Rahma; Annur, Saipul; Hendrik, Deny (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
institutions will be able to increase public interest in the educational services offered. To be able to realize this, educational institutions need a strategy so that this can be achieved. The strategies needed include positioning and differentiation related to educational services. This article aims to discuss everything related to positioning and differentiation of Islamic education services. The method used in this paper is a literature review or literature study which contains theories that are relevant to the problems that will be discussed, the study is explained regarding the concepts and theories used based on available literature, from books and articles that has been published in a scientific journal. The results of this article regarding positioning and differentiation of educational services are that these two things can be said to be two interrelated things, because positioning is a positioning for educational institutions to show their position to the wider community with a good and positive image and worthy of their services being used. , while differentiation is about the methods or strategies used by educational institutions to be able to provide a more unique difference from competitors or other educational institutions, so that this difference can attract the interest of consumers (the public) who are then interested in using the services of educational institutions.